Preliminary Study of Geo-Magnetic Phenomena at The Arjuno–Welirang Volcano, Indonesia - Adinda Salsabilla Raindraputri Hidayat; Sukir Maryanto; Faridha Aprilia; Elizza Inaya Permata Sari; Athorhab, Iskara Hadijah Aqila Nasywa Rastramata (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Mount Arjuno–Welirang is an active volcano in East Java that exhibits volcanic activity in the form of shallow and deep earthquakes, as well as fumarolic emissions. This study aims to monitor the subsurface dynamics of the volcano through the integration of magnetic and seismic methods. Magnetic field measurements were carried out using a proton precession magnetometer to obtain local magnetic anomalies after applying diurnal corrections, IGRF correction, and regional–residual anomaly separation. The RTP and residual maps reveal high-anomaly zones that are interpreted as shallow magma intrusions, as well as low-anomaly zones associated with hydrothermal alteration and fracturing. These interpretations are integrated with the lithology of the Qvaw Formation, which consists of lava, volcanic breccia, and tuff. In addition, MAGDAS data were used to analyze diurnal geomagnetic variations (H, D, Z), which show significant fluctuations during certain periods, indicating local geomagnetic disturbances likely influenced by seismic activity or subsurface geological processes. The combination of magnetic and seismic methods provides a more comprehensive understanding of magma pathways, hydrothermal fluid dynamics, and potential increases in volcanic activity, thereby supporting disaster mitigation efforts in the Arjuno–Welirang region.